(3QSGdI aj GdMHI GdShOGA ef TQM GdTjN RQhbs - (3CMeO Hf RQhb GdaGSj, RQhb,J (B899 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI bGd GdfHj Udi Gddg Ydjg hSde (B: (3Ef aj GdLfI GdShOGA TaGA ef cd OGA EdG GdSGe hGdeQGO ef GdMOjK aj GdMHI GdShOGA s
(3BNQgG (B:s
(3EPG fVGa dgG TF ef GdRfLHjd eObhbkG GfJgj ef TQM GdTjN RQhb s
(3Vef eLehY , JQJjHgG (B: 13s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3eUOQ GbJfGA GdCUd (B:s
(3eQcR GdHMK GdYdej (B- (3Ge GdbQj s
Keywords: (3eJaQbGJs